Light‐harvesting superstructures of green plant chloroplasts lacking photosystems. (23rd April 2015) - Belgio, Erica; Ungerer, Petra; Ruban, Alexander V.
Abstract The light‐harvesting antenna of higher plant photosystem II (LHCII) is the major photosynthetic membrane component encoded by an entire family of homologous nuclear genes. On the contrary, the great majority of proteins of photosystems and electron transport components are encoded by the chloroplast genome. In this work, we succeeded in gradually inhibiting the expression of the chloroplast genes that led to the disappearance of the photosystem complexes, mimicking almost total photoinhibition. The treated plants, despite displaying only some early signs of senescence, sustained their metabolism and growth for several weeks. The only major remaining membrane component was LHCII antenna that formed superstructures – stacks of dozens of thylakoids or supergrana. Freeze‐fracture electron microscopy revealed specific organization, directly displaying frequently bifurcated membranes with reduced or totally absent photosystem II (PSII) reaction centre complexes. Our findings show that it is possible to accumulate large amounts of light‐harvesting membranes, organized into three‐dimensional structures, in the absence of reaction centre complexes. This points to the reciprocal role of LHCII and PSII in self‐assembly of the three‐dimensional matrix of the photosynthetic membrane, dictating its size and flexible adaptation to the light environment.